Gambaran squamous cell carcinoma posterior mandibula pada radiograf panoramik - Gunawan Gunawan; Ria Noerianingsih Firman; Farina Pramanik; Aga Satria Nurrachman (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2020)
Objectives: This study is aimed to report a case of mandibular left posterior squamous cell carcinoma on panoramic radiographs. Case Report: A 61 years male patient came to the RSGM UNPAD Radiology Installation carrying a referral letter to have panoramic examination. The patient had his molars extracted one year ago, but then six months later he complained of swelling. Since one week ago he has been feeling pain and difficulty opening my mouth, premedication of amoxicillin and paracetamol has been given. Extra oral examination showed facial asymmetry, swelling, intra-oral examination of swelling, redness accompanied by ulceration. A panoramic radiograph showed loss of left molar teeth, radiointermediate area in the left posterior region of the mandible ± 5 cm, radiolucent ill-defined non-corticated, irregular in the posterior mandibular body. Conclusion: Panoramic radiographs can be used as a supportive examination of SCC cases which show the presence of an ill-defined non-corticated radiointermediate area, irregular bone invasion